Biology and fishery of Panulirus gracilis (Streets 1871) (Decapoda: Palinuridae) in the Panama’s Western Pacific - Vega, Ángel J. (2013)
The Pacific spiny lobster (Panulirus gracilis) is an important fishery resource from the Western Pacific region of Panama. Between October 2005 and April 2007, the Gulf of Montijo lobster population was sampled to determine total length (LT), cephalothorax length (LC), abdominal length (LA), total weight, sex, gonadal development, and frequency of gravid females. Furthermore, lobster landing volumes from the Gulf of Chiriquí National Marine Park were used to estimate the catch per unit effort (CPUE) (kg of lobster landed / fisherman-week) between 2000 and 2009. Lobster LT in the Gulf of Montijo (average ± SD) was 206 ± 31 mm and females were significantly larger in size and weight than males. The cumulative frequency of cephalothorax and abdominal lengths indicated that a high percentage of catches occur below the minimum legal size when regulation is applied measuring the abdomen (112 mm). Incidence of such cases is greater in males than in females. This difference might be a consequence of a regulation lacking morphometric data for P. gracilis and the assumption that the abdominal length is twice the cephalothorax length. Females with mature gonads and eggs were observed throughout the sampling period, which is indicative of continuous reproduction. Sex ratio was male biased (1.31:1). Between 2000 and 2009 there was an important reduction in volume and CPUE.